Reversibly thermosecreting and convertible lubricative oil-in-water mixtures using multiple hydrogen bonding interactions - Qianhui Zhou; Mingfei Li; Weiyan Yu; Yunjing Wang; Yujie Yang; Jingcheng Hao; Lu Xu (Communications Materials)
Abstract Achieving homogeneous oil and water mixing requires thorough droplet dispersions of both liquids. An additional component, such as a surfactant, particle, solvent or ion is normally required to stabilize the small liquid droplets by providing sufficiently low interfacial tensions or strong repulsive forces. Here we show that very stable oil-in-water mixtures can be created even at very high oil volume fractions by building multiple, high-strength hydrogen bonding interactions between water and a biocompatible and biodegradable oil trimethylolpropane trioleate, which make the oil molecules at the contact interface behave as pseudo-surfactants with ultrahigh interfacial activity. The resultant oil microdroplets can be reversibly thermosecreted from the continuous aqueous phase and lead to controllable formation/dissociation and switchable lubrication of the binary liquid mixture owing to the inherent thermal responsiveness of the intermolecular hydrogen bonding. Interestingly, although water is uncovered to possess a relatively poor lubricity, the liquid mixture yields an optimized lubrication that is even exceedingly comparable to pure oil at a water volume fraction as high as 80%.